2018
DOI: 10.5897/ajar2018.13097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of energy input-output of irrigated rice production in Jere Bowl Borno State, Nigeria

Abstract: The study analyzed energy input-output of irrigated rice production at the Jere Bowl Borno State, Nigeria. One hundred and thirty farms were sampled through multistage sampling procedure. The data collected were analyzed using descriptive statistics and energy equations. The result showed that total of 36,397.85 MJ/ha of energy was consumed in the irrigated rice production with the highest energy input taken up by irrigation water (48.51%) and fuel (23.58%). The forms of energy estimated showed that direct ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…The result was consistent with the findings of Effiom and Ebi (2021), who reported that the liberalisation policy restricts the long-term growth of the value-added produced by the agricultural sector. However, these findings negate the earlier studies of Felix et al (2013a, b) and Muhammad and Atte (2006), who reported that trade liberalisation promotes the economic growth in Nigeria with positive developmental support in its agricultural sector. According to Effiom and Ebi (2021), key infrastructure elements (telecommunications, roads and electricity consumption) had a significant relationship with and positively affected the agricultural sector.…”
Section: Impacts Of Trade and Economic Policies On The Nigerian Agric...contrasting
confidence: 92%
See 1 more Smart Citation
“…The result was consistent with the findings of Effiom and Ebi (2021), who reported that the liberalisation policy restricts the long-term growth of the value-added produced by the agricultural sector. However, these findings negate the earlier studies of Felix et al (2013a, b) and Muhammad and Atte (2006), who reported that trade liberalisation promotes the economic growth in Nigeria with positive developmental support in its agricultural sector. According to Effiom and Ebi (2021), key infrastructure elements (telecommunications, roads and electricity consumption) had a significant relationship with and positively affected the agricultural sector.…”
Section: Impacts Of Trade and Economic Policies On The Nigerian Agric...contrasting
confidence: 92%
“…Government help to the agricultural sector is concentrated on providing inputs, extension services, market price regulation for specific items through a strategic reserve strategy and monetary support, although at a limited level. Despite these aids, the contributions of agriculture to the nation’s economic development have decreased gradually over the years, mainly due to the rising value of food imports (Figure 5; Manyong et al 2005; Muhammad and Atte 2006; Umoh and Ekpo 2012). As a result, the government instituted many agricultural initiatives and policies to increase agricultural productivity in Nigeria.…”
Section: Impacts Of Trade and Economic Policies On The Nigerian Agric...mentioning
confidence: 99%